Verbatim++: verified, optimized, and semantically rich lexing with derivatives. - Egolf, Derek.; Lasser, Sam.; Fisher, Kathleen. (Tufts University. Tisch Library., 2023)
Keywords: Brzozowski derivatives, formal verification, lexical analysis, semantic actions.; Topic: Security and privacy / Formal methods and theory of security / Logic and verification; Topic: Theory of computation / Formal languages and automata theory / Regular languages; Topic: Software and its engineering / Software notations and tools / Compilers / Parsers; ACM Open.